Safety and immunogenicity of a 30-valent M protein-based group a streptococcal vaccine in healthy adult volunteers: A randomized, controlled phase I study. Issue 6 (5th February 2020) - Pastural, Élodie; McNeil, Shelly A.; MacKinnon-Cameron, Donna; Ye, Lingyun; Langley, Joanne M.; Stewart, Robert; Martin, Luis H.; Hurley, Gregory J.; Salehi, Sanaz; Penfound, Thomas A.; Halperin, Scott; Dale, James B.
Abstract: Background: Streptococcus pyogenes (group A Streptococcus, Strep A) is a widespread pathogen that continues to pose a significant threat to human health. The development of a Strep A vaccine remains an unmet global health need. One of the major vaccine strategies is the use of M protein, which is a primary virulence determinant and protective antigen. Multivalent recombinant M protein vaccines are being developed with N-terminal M peptides that contain opsonic epitopes but do not contain human tissue cross-reactive epitopes. Methods: We completed a Phase I trial of a recombinant 30-valent M protein-based Strep A vaccine (Strep A vaccine, StreptAnova™) comprised of four recombinant proteins containing N-terminal peptides from 30 M proteins of common pharyngitis and invasive and/or rheumatogenic serotypes, adjuvanted with aluminum hydroxide. The trial was observer-blinded and randomized in a 2:1 ratio for intramuscular administration of Strep A vaccine or an alum-based comparator in healthy adult volunteers, at 0, 30 and 180 days. Primary outcome measures were assessments of safety, including assays for antibodies that cross-reacted with host tissues, and immunogenicity assessed by ELISA with the individual vaccine peptides and by opsonophagocytic killing (OPK) assays in human blood. Results: Twenty-three Strep A-vaccinated participants and 13 controls completed the study. The Strep A vaccine was well-tolerated and there was no clinical evidence of autoimmunity and no laboratory evidence of tissue cross-reactive antibodies. The vaccine was immunogenic and elicited significant increases in geometric mean antibody levels to 24 of the 30 component M antigens by ELISA. Vaccine-induced OPK activity was observed against selected M types of Strep A in vaccinated participants that seroconverted to specific M peptides. Conclusion: The Strep A vaccine was well tolerated and immunogenic in healthy adults, providing strong support for further clinical development. [ClinicalTrials.gov NCT02564237].